American tegumentary leishmaniasis: an uncommon clinical and histopathological presentation Leishmaniose tegumentar americana: uma apresentação clínica e histopatológica incomum - Adrilena Lopes Adriano; Paula Azevedo Borges Leal; Marcelle Parente Breckenfeld; Igor dos Santos Costa; Clarisse Almeida; Antônio Renê Diógenes de Sousa (Sociedade Brasileira de Dermatologia, 2013)
We report a case of an unusual presentation of American Tegumentary Leishmaniasis involving a male patient with a solitary lesion on the ear lobe, persisting with minimal increase for at least six months without ulceration or related symptoms. The histological sections showed epithelial atrophy and a large number of structures consistent with Leishmania sp. amastigotes within macrophages. Treatment commenced with meglumine antimoniate resulting in regression of the condition. This report is of importance given the unusual clinical manifestation and histopathological findings in this case and the fact that there was low correlation with the extended duration of the disease. Relatamos um caso de apresentação incomum de leishmaniose tegumentar americana com lesão solitária no lóbulo da orelha de um paciente do sexo masculino com mínimo aumento em, pelo menos, seis meses, sem ulceração ou sintomas relacionados. Os cortes histológicos mostraram atrofia epitelial e um grande número de estruturas compatíveis com amastigotas de Leishmania sp. no interior de macrófagos. O tratamento foi iniciado com antimoniato de meglumina, com regressão do quadro. A importância desse relato de caso é devido à apresentação clínica e histopatológica atípica e sua baixa correlação com a duração prolongada da doença.